(untitled) (Journal of Pharmaceutical Negative Results, 2023)
Breastfeeding is the feeding of an infant or young child with breast milk directly from female human breasts rather than from baby bottle or other container. The World Health Organization and the American Academy of Paediatrics emphasize the value of breastfeeding for mothers as well as children. Both recommend exclusive breast feeding for the first six months of life including sick newborns and preterm infants. Pre experimental design was adapted for conducting the study. This study was conducted in Sri Venkateshwaraa Medical College and Research Institute, Puducherry. Sample included 40 working lactating women, who were selected by non-probability convenient sampling technique. Demographic Data was collected using Self-administered questionnaire and Structured knowledge questionnaire was used to assess the knowledge and structured rating scale was used to assess the attitude regarding technique on expressing and utilization of expressed breast milk among working lactating women .The educational intervention was given about importance of expressed breast milk, methods, preservation techniques to experimental group with the flip chart. The post test was done with same tool after 4 days. The result of this study concluded that the educational intervention was effective in improving the knowledge (t value was 33.84 at the p <0.05) and attitude (t value was 23.86 at the p <0.05) regarding technique on expressing and utilization of expressed breast milk among working lactating women.